(696) Some Problems of Constructing the Long-Term Projection in Czechoslovakia بعض مشاكل بناء التوقعات طويلة الأمد في تشيكوسلوفاكيا - Spevacek, Vojtech (معهد التخطيط القومى, 2025)
The text discusses the challenges and opportunities of applying economic and social development strategies in different regions. It highlights the importance of practical experience and economic models to address challenges and achieve long-term goals. The focus is on integrating localized solutions into broader national planning, particularly in socialist economies, to improve economic performance and government responsiveness. The significance of aligning these strategies with both theoretical models and real-world conditions is emphasized. /